Robust Standard Error Estimators for Panel Models: A Unifying Approach - Millo, Giovanni (Journal of Statistical Software, 2017)
The different robust estimators for the standard errors of panel models used in applied econometric practice can all be written and computed as combinations of the same simple building blocks. A framework based on high-level wrapper functions for most common usage and basic computational elements to be combined at will, coupling user-friendliness with flexibility, is integrated in the plm package for panel data econometrics in R. Statistical motivation and computational approach are reviewed, and applied examples are provided.